2012
DOI: 10.1016/j.jesp.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Listeners' eyes reveal spontaneous sensitivity to others' perspectives

Abstract: very little is known about the time-course with which such perspective information influences communication. We report a novel interactive Ôvisual worldÕ study examining these processes. Here, two communicators watched videos depicting transfer events and subsequently described these events to each other. Critically, on half the trials a screen blocked the speakersÕ (but not the listenersÕ) view part-way through the video, establishing a discrepancy in the knowledge held by the two communicators. Eye-tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
(39 reference statements)
6
36
0
Order By: Relevance
“…"with the spots on"), and thus chose not to deploy perspective-taking at all until this disambiguating information had become available. This account is consistent with previous research, which has shown that while listeners are spontaneously sensitive to others' perspectives, they can be delayed in the explicit use of this information to predict others' actions (Ferguson & Breheny, 2012;Ferguson et al, 2015), however it contrasts with other studies in which participants do not delay perspective use until a temporary ambiguity is resolved (e.g. Brown-Schmidt et al, 2008;Heller et al, 2008).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…"with the spots on"), and thus chose not to deploy perspective-taking at all until this disambiguating information had become available. This account is consistent with previous research, which has shown that while listeners are spontaneously sensitive to others' perspectives, they can be delayed in the explicit use of this information to predict others' actions (Ferguson & Breheny, 2012;Ferguson et al, 2015), however it contrasts with other studies in which participants do not delay perspective use until a temporary ambiguity is resolved (e.g. Brown-Schmidt et al, 2008;Heller et al, 2008).…”
Section: Methodssupporting
confidence: 90%
“…Similarly, tasks in which the participant is a passive observer to narrated events in a discourse have shown rapid and accurate prediction of other peoples' actions based on an understanding of their (false) beliefs (e.g. Ferguson & Breheny, 2012;Ferguson, Scheepers, & Sanford, 2010;Rubio-Fernández, 2013), or conflicting desires (Ferguson & Breheny, 2011). These studies, showing early use of perspective, suggest that interpretation of language is driven by multiple probabilistic constraints, one of which is perspective (Brown-Schmidt & Hanna, 2011).…”
mentioning
confidence: 94%
“…Apperly, Back, Samson, & France, 2008;Keysar et al, 2000Keysar et al, , 2003 and pervasive effects of 25 own knowledge (e.g. Birch & Bloom, 2007;Ferguson, Apperly, Ahmad, Bindemann, & Cane, 2015;Ferguson & Breheny, 2012;Mitchell et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For a given conversational participant, determining what information is likely shared and what is privileged is itself a complex process that draws on multiple sources of information such as community membership as well as the situational and linguistic context (Clark & Marshall, 1981) and, accordingly, entails various cognitive demands. Consequently, one question that is still widely discussed in contemporary work on real-time referential processing involves the extent to which shared and privileged knowledge are effectively differentiated in the earliest moments of comprehension (e.g., Barr, 2008b;Brown-Schmidt, 2012;Brown-Schmidt, Gunlogson, & Tanenhaus, 2008;Ferguson & Breheny, 2011;Ferguson & Breheny, 2012;Hanna & Tanenhaus, 2004;Hanna, Tanenhaus, & Trueswell, 2003;Heller, Grodner, & Tanenhaus, 2008;Keysar, Barr, Balin, & Brauner, 2000;Keysar, Barr, & Horton, 1998;Keysar, Lin, & Barr, 2003;Lin, Keysar, & Epley, 2010).…”
Section: Introductionmentioning
confidence: 99%